Upper Paleozoic to Lower Mesozoic Tetrapod Ichnology Revisited: Photogrammetry and Relative Depth Pattern Inferences on Functional Prevalence of Autopodia - Mujal, Eudald; Marchetti, Lorenzo; Schoch, Rainer R.; Fortuny, Josep (Frontiers in Earth Science, 2020)
In recent years photogrammetry has become an essential tool in the study of tetrapod footprints. Morphological analyses of footprints are interpretative; thus, researchers should use as much information as possible in order to eventually provide an objective conclusion. In this regard, photogrammetry is an extremely helpful tool to avoid potential biases and to better present ichnological data. We review the use of this technique in several Permian and Triassic tetrapod ichnological studies, with considerations on (1) ichnotaxonomy, (2) track-trackmaker correlation, (3) locomotion and/or behavior, (4) substrate induced effects, and (5) preservation of the fossil record and heritage. Furthermore, based on the available three-dimensional (3D) data on Permian and Triassic material, we present a first qualitative interpretation of relative depth patterns and the related functional prevalence (most deeply impressed area) within footprints. We identified three main groups: (1) anamniote, captorhinomorph/parareptile tracks (medial-median functional prevalence), (2) diapsid tracks (median functional prevalence), and (3) synapsid tracks (median-lateral functional prevalence). The use of 3D photogrammetric models brings new light to the tetrapod footprint record, helping to better understand tetrapod communities throughout the late Paleozoic (and the end-Guadalupian and end-Permian extinctions) and the tetrapod recovery during the early Mesozoic.